Germ Cell Tumors of the Ovary: A Review of 644 Cases - Pavit Sutchritpongsa; Peerapong Inthasorn; Prasong Tunmahasamut; Noavaratana Singto; Ampan Netphisuth (Siriraj Medical Journal, 2020)
This retrospective study reports 644 female patients with germ cell tumors of the ovary treated at Siriraj Hospital over a ten-year period from 1988-1997. The incidence was 38.7% of all ovarian tumors (1,665 cases). Of the total, 608 patients (94.4%) had benign cystic teratomas and only 36 patients (5.6%) had malignant tumors. Dysgerminoma was the most common malignant germ cell tumor. Germ cell tumor was the most common malignant ovarian tumor in patients less than 20 years old. The mean age and parity of patients with benign tumor was significantly higher than those with malignant tumors (p<0.01). Benign tumors were often asymptomatic (35%) when the tumors were discovered but those with malignant tumors usually had symptoms and the most common symptoms was a palpable abdominal mass (47.2%). In the cases with benign tumors, more than two-thirds (73.7%) had a tumor less than 10 cm in length, but more than half (66.7%) of the patients with malignant tumors had an intermediate tumor between 11 and 20 cm long. Most of the patients in both groups had a unilateral tumor (p>0.05). Surgical treatment was conservative in 63.8% of patients with benign tumors, while only 30.6% of those with malignant tumors underwent conservative surgery (p<0.05).